Nb-doped Ga2O3 as charge-trapping layer for nonvolatile memory applications. (October 2016) - Shi, R.P.; Huang, X.D.; Sin, Johnny K.O.; Lai, P.T.
Abstract: The charge-trapping properties of Nb-doped Ga2 O3 are investigated by using an Al/Al2 O3 /GaNbO/SiO2 /Si structure. Compared with the memory capacitor with pure Ga2 O3, the one with lightly Nb-doped Ga2 O3 shows better charge-trapping characteristics, including larger memory window (5.5 V at ± 6 V sweeping voltage), higher programming and erasing speeds due to its higher trapping efficiency resulted from increased trap density induced by the Nb doping. The sample with heavily Nb-doped Ga2 O3 also shows improvements compared with the one with pure Ga2 O3, but not as large as those for the lightly Nb-doped sample due to defects generated by excessive Nb doping. Erase saturation phenomenon is observed in all the samples, and can be suppressed by hole traps created by the Nb doping. Highlights: Lightly Nb-doped Ga2 O3 shows good charge-trapping properties. The Nb doping suppresses Ga diffusion into SiO2 . The Nb doping increases the trap density of Ga2 O3 . The Nb doping increases the k value of Ga2 O3 .